Cost Analysis with Activity Based Costing Method on Coronary Heart Catheterization at Dr. Sardjito Hospital Yogyakarta - Nugroho Bayu Aji; Rizal Yaya; Wiwik Kusumawati (Universitas Muhammadiyah Yogyakarta, 2018)
The purpose of this study was to calculate unit cost coronary angiography with the ABC method and analyze the differences in the results of the calculation unit cost of the ABC method with the current rates at RSUP Dr. Sardjito Yogyakarta. The research method is qualitative with a descriptive design case study, this study uses primary data and secondary data. Primary data is in the form of interviews, while secondary data is obtained through financial data in 2016. Methods for analyzing costs using the method of Activity Based Costing (ABC). The study resulted that coronary angiography-guided by the SPO, the results of the calculation unit cost of the ABC method were Rp7.927.171,13 higher than the current fare. The unit cost of coronary angiography at RSUP Dr. Sardjito Yogyakarta by the ABC method is a unit cost for coronary angiography without difficulty which is calculated by charging all costs both direct costs and costs overhead. Hospital rates have not been recalculated since 2014, so it has not yet described the real conditions in 2016. In addition, personnel expenditure conditions that exceed the provisions of the proportion of a maximum of 44% as mandated in the Republic of Indonesia Minister of Health Regulation are the factors causing higher unit cost calculation ABC method rather than rates coronary-angiography hospital.